Shamba Maisha: randomized controlled trial of an agricultural and finance intervention to improve HIV health outcomes. (10th September 2015) - Weiser, Sheri D.; Bukusi, Elizabeth A.; Steinfeld, Rachel L.; Frongillo, Edward A.; Weke, Elly; Dworkin, Shari L.; Pusateri, Kyle; Shiboski, Stephen; Scow, Kate; Butler, Lisa M.; Cohen, Craig R.
Abstract : Objectives: Food insecurity and HIV/AIDS outcomes are inextricably linked in sub-Saharan Africa. We report on health and nutritional outcomes of a multisectoral agricultural intervention trial among HIV-infected adults in rural Kenya. Design: This is a pilot cluster randomized controlled trial. Methods: The intervention included a human-powered water pump, a microfinance loan to purchase farm commodities, and education in sustainable farming practices and financial management. Two health facilities in Nyanza Region, Kenya were randomly assigned as intervention or control. HIV-infected adults 18 to 49 years' old who were on antiretroviral therapy and had access to surface water and land were enrolled beginning in April 2012 and followed quarterly for 1 year. Data were collected on nutritional parameters, CD4 + T-lymphocyte counts, and HIV RNA. Differences in fixed-effects regression models were used to test whether patterns in health outcomes differed over time from baseline between the intervention and control arms. Results: We enrolled 72 and 68 participants in the intervention and control groups, respectively. At 12 months follow-up, we found a statistically significant increase in CD4 + cell counts (165 cells/μl, P  < 0.001) and proportion virologically suppressed in the intervention arm compared with the control arm (comparative improvement in proportion of 0.33 suppressed, odds ratio 7.6, 95% confidence interval: 2.2–26.8). Intervention participants experienced significant improvements in food security (3.6 scale points higher, P  < 0.001) and frequency of food consumption (9.4 times per week greater frequency, P  = 0.013) compared to controls. Conclusion: Livelihood interventions may be a promising approach to tackle the intersecting problems of food insecurity, poverty and HIV/AIDS morbidity. Abstract : Supplemental Digital Content is available in the text